The fighting season - Connolly, Bram (Allen & Unwin, 2016)
Introducing Matt Rix... Australian commando. An explosive thriller from the heart of Afghanistan. Step aside Andy McNab and Chris Ryan, there's a new special forces operator out there - ultra lethal, ultra tough, and all Australian...Outside the wire, Uruzghan Province, Afghanistan, 2010.....In the badlands of central Afghanistan an Australian Special Forces platoon is fatally hit by a roadside bomb...A shadowy Taliban commander, codenamed 'Rapier', is identified as responsible for the deadly attack. Matt Rix, the ultra tough commando who led the ambushed platoon swears vengeance. Rix is one of Special Forces' most lethal operators